A bifunctional metal–organic framework platform for catalytic applications. (1st February 2019) - Müller, Philipp; Bon, Volodymyr; Senkovska, Irena; Nguyen, Khoa D.; Kaskel, Stefan
Graphical abstract: DUT-71 was used as a platform for postsynthetic modification to enhance the catalytic activity of MOF in Hanry reaction. Abstract: DUT-71 (DUT – Dresden University of Technology), a copper paddle wheel based framework, was used as a platform for postsynthetic modification to introduce specific catalytically active sites and to enhance the catalytic activity for fine chemicals production using bifunctional N-donor ligands such as dabco (1, 4-diazabicyclo[2.2.2]octane) and 3, 5-bis(1 H -imidazol-1-yl)arene derivatives resulting in the corresponding networks DUT-72 and DUT-90. The intact network structure after functionalisation was confirmed by powder X-ray diffraction, the degree of functionalization was analysed by 1 H NMR, thermal and elemental analysis. As a model reaction, the CC coupling reaction of Henry type catalysed by Lewis acids in presence of organic base was chosen. The influence of the functionalisation degree, solvent, and reaction temperature on the catalytic activities was studied. Finally, yields up to 77% of 2-nitro-1-(4-nitrophenyl)ethan-1-ol in the reaction of 4-nitrobenzaldeyde with nitromethane were achieved using a dabco functionalised network DUT-72.